Strategi Sosialisasi Kebijakan Penderekan oleh Suku Dinas Perhubungan Jakarta Barat - Vania Utamie Subiakto (CoverAge: Journal of Strategic Communication, 2019)
This research was conducted as a way to uncover the socialization strategy of towing policies through social media by the West Jakarta Transportation Department, through a case study perspective. This is a way to socialize DKI Jakarta Regional Government Regulation No. 5 of 2014. This study uses a qualitative research method with a case study approach and a contrutivism paradigm. The theories used are Communication Management, Planning, and SWOT Analysis. The results that are known from this study are about four things as follows: 1). Planning for the socialization of the towing policy strategy by the West Jakarta Transportation Agency. 2). The source of the socialization strategy for towing policies by the West Jakarta Transportation Agency. 3). Obstacles to the socialization of the towing policy strategy by the West Jakarta Transportation Agency .; and 4) The description of the audience of the socialization of the towing policy by the West Jakarta Transportation Department.